PERCEPTION AND EXPECTATION THE SOCIETY OF CONFLICT WITH PT. DUTA PALMA NUSANTARA IN BANJAR BENAI VILLAGE BENAI DISTRICT KUANTAN SINGINGI REGENCY - Habibie, Muhammad Husni Yusnizar; Sayamar, Eri; ', Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research are: (1) to know the perception of Banjar Benai Village’s society about conflict understanding with PT. Duta Palma Nusantara; and (2) to know the expectation of Banjar Benai Village’s society about conflict understanding with PT. Duta Palma Nusantara. This research used survey method. The sampling method in this research used snowball method.The first purpose answered with qualitative descriptive analysis used 5W + 1H question. The second purpose to analyze the expectation of society can be measured with Likert’s Summated Rating Scale (SLRS). The result of this research was got from the society perception in Banjar Benai village with PT. Duta Palma Nusantara. It can be seen from 5W + 1H with sub variable perception to problem of the conflict, perceptions to the goal of conflict subject and perception of conflict subject. The conflict that occured between PT. Duta Palma Nusantara and society has persist. It start from the cultivate right and companies contract that not clear. Since 2004 until now there has been no settlement for this conflict. The third side of local government has been presented to clear that conflict, but the government it also can not to solved the conflict between the society and the company. The level of the society expectation with PT. Duta Palma Nusantara was in the high category perception. It can be seen in 3,71 scores were comparised of the sub goal variable, pathway thinking and agency thinking. Keywords: Conflict, Perceptions, and Expecations